2017
DOI: 10.20964/2017.06.92
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Studies of Adsorption Characteristics of Newly Synthesized Schiff Bases and their Evaluation as Corrosion Inhibitors for Mild Steel in 1 M HCl

Abstract: A new class of Schiff base compounds viz., 4,4'-bis(2,4-dihydroxybenzaldeyde) diphenylethanediimine (L1) and 4,4'-bis(4-diethlylaminosalicylaldehyde) diphenylethanediimine (L2) have been synthesized and characterized by spectral techniques using Elemental analysis, FTIR, 1 H-NMR and mass spectrometry. The inhibition action on corrosion of the Schiff bases on mild steel in 1 M hydrochloric acid has been studied by the weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 98 publications
1
7
1
Order By: Relevance
“…The impedance spectra showed the single semicircle and the diameter of semicircle increases with increasing concentration of the inhibitor [50]. The semicircles show slight irregularity which may be attributed to the roughness, impurities, dislocations, or non-homogeneous nature of the metal surface [51][52][53][54][55][56]. The capacitance loop intersects the real axis at higher and lower frequencies.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…The impedance spectra showed the single semicircle and the diameter of semicircle increases with increasing concentration of the inhibitor [50]. The semicircles show slight irregularity which may be attributed to the roughness, impurities, dislocations, or non-homogeneous nature of the metal surface [51][52][53][54][55][56]. The capacitance loop intersects the real axis at higher and lower frequencies.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Calculated data are given in Table 6 From Table 6, it was found that the HOMO and the LUMO changed rulelessly, while it was observed that the highest value of calculated ΔE was obtained by A316 and the lowest energy gap value was that of A312. It is well known that the lower the values of energy gap, the better the corrosion inhibition, because the ionization potential will be low [38][39][40][41]. This behavior pointed to that the shorter the chain length of the hydrophobic part, the lower the energy gap ΔE and the higher the inhibition efficiency of the Gemini surfactant, because the energy needed to remove an electron from the last occupied orbital will be low, which facilitates adsorption (and therefore inhibition), and that agrees well with the experimental findings.…”
Section: Computational Studymentioning
confidence: 99%
“…There is no agreement in the literature on the use of dipole moment ( ) as a predictor for the trend of the inhibition reaction. Some authors reported that the high values of the dipole moment pointed to high inhibition efficiency [41][42][43].…”
Section: Computational Studymentioning
confidence: 99%
“…Mild Steel (MS) is extensively used in many industries such as tanks and water utilities, power production, heat exchangers, oil, chemical, and electrochemical technologies due to good mechanical strength and relatively low price, but it is susceptible to several forms of corrosion in some environments especially in the acidic environment (1,2). This phenomenon can be minimized or delayed by various means such as coatings, cathodic protection, and corrosion inhibitors (3). Corrosion inhibitors, classified as inorganic and organic types, are one of the most cost-effective methods for controlling corrosion.…”
Section: Introductionmentioning
confidence: 99%